Pengaruh Edukasi dan Perawatan Kaki terhadap Pencegahan Luka Kaki Diabetik - Rizki Hidayat; Pradana Soewondo; Dewi Irawaty (Malahayati Nursing Journal, 2022)
ABSTRACT Diabetic foot ulcer (DFU) is classified as an incurable chronic wound that causes skin irritation with a long and frustrating healing process. DFU can be prevented and the frequency of lower extremity amputations can be reduced by 49-87% by preventing the development of DFU. Evidence in the literature suggests that early detection and treatment of diabetic foot complications can reduce the prevalence of ulceration by 44% to 85%. Foot care, especially diabetes, is becoming a new standard of care and the mainstay of therapy in preventing the development of DFU. To See The Effect Of The Combination Of Education And Foot Care Model On The Prevention Of Diabetic Foot Wounds. Systematic Review, through systematic searches on 9 databases (Hindawi, Pubmed, Researchgate, Science Direct, Journal of diabetes metabolism, National Public Health Journal, American Journal of Nursing Science, International Journal of Foot and Ankle). published since 2010, Of the 30 references that have been identified, 30 references have been examined in detail, of that number, 12 research references meet the inclusion and exclusion criteria, all of which contain instruments relevant to the variables in this systematic review. From 12 References Used The Results Show Foot Education and Care Affect the Healing Process of Diabetic Foot Wounds. Diabetic foot ulcers are a complication of diabetes mellitus and have complex problems so that the wound is difficult or delays wound healing, prevention with education and foot care is very helpful to avoid this condition, especially in reducing the risk in wound prevention. Keywords:  Diabetic Foot Wound, Education, Foot Care, Wound Prevention  ABSTRAK Diabetic foot ulcer (DFU) diklasifikasikan sebagai luka kronis yang tidak dapat disembuhkan yang menyebabkan gangguan pada kulit dengan proses penyembuhan yang lama dan frustrasi. DFU dapat dicegah dan frekuensi amputasi ekstremitas bawah dapat diturunkan hingga 49-87% dengan mencegah perkembangan DFU. Bukti dalam literatur menunjukkan bahwa deteksi dini dan pengobatan komplikasi kaki diabetik dapat mengurangi prevalensi ulserasi sebesar 44% hingga 85% (Wirsing, 2015). Perawatan kaki khususnya diabetes menjadi standar perawatan baru dan terapi andalan dalam mencegah perkembangan DFU. Untuk Melihat Pengaruh Model Kombinasi Edukasi Dan Perawatan Kaki Terhadap Pencegahan Luka Kaki Diabetik. Sistematika Review, melalui penelusuran secara sistematis pada 9 database (Hindawi, Pubmed, Researchgate, Science Direct, Jurnal Of diabetes metabolism, National Public Health Jurnal, American Journal Of Nursing Science,  International Jurnal Of Foot and Ankle). yang dipublikasikan sejak tahun 2010, Dari 30 jumlah referensi yang telah diidentifikasi, ada 30 referensi yang diperiksa dengan detail, dari jumlah tersebut, terdapat 12 referensi penelitian yang memenuhi kriteria inklusi dan eksklusi , dimana seluruhnya memuat instrument yang relevan dengan variabel pada sistematika review ini . Dari 12 Referensi Yang Digunakan  Hasil Nya Menunjukkan Edukasi dan perawatan kaki Mempengaruhi Proses Penyembuhan Luka Kaki Diabetik. Luka kaki diabetic merupakan Kompilkasi dari diabetes militus serta mengalami kompleksitas masalah sehingga luka sulit atau mengalami penundaan penyembuhan luka, pencegahan dengan edukasi dan perawatan kaki  sangat membantu untuk menghindari kondisi tersebut, terutama dalam menurunkan resiko dalam pencegahan luka. Keyword: Luka Kaki Diabetic, Edukasi, Perawatan Kaki, Pencegahan Luka.